2021
DOI: 10.1515/fjsb-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Die Zivilgesellschaft in der Krise

Abstract: Zusammenfassung Dieser Beitrag präsentiert erste Einblicke in eine Organisationsbefragung zur Auswirkung der COVID-19 Pandemie auf Vereine und Initiativen in Deutschland. Die Studie unterstreicht, dass die Zivilgesellschaft mit großer Wucht getroffen wurde und weitreichende, negative Auswirkungen der Pandemie zu verzeichnen sind. Dennoch zeigen die Ergebnisse ebenfalls, dass sich Teile der Zivilgesellschaft der pandemischen Entwicklung anpassen und ihre Handlungsfähigkeit aufrechterhalten konnte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Considering this crisis, our quantitative data for all organizations show that single activities did not come to a complete standstill, but could be continued to a lesser extent and, in some cases, almost to the same degree as before March 2020. Our data on the activities for the second and third pandemic year thus differ overall from a quantitative survey on the impact of the COVID-19 pandemic on the activities of civic associations in 2020, that is, in the first pandemic year (Hutter et al 2021). Here, it was found that activities in the areas of recreation, education, counseling, culture, and protest had to be severely restricted or stopped altogether.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Considering this crisis, our quantitative data for all organizations show that single activities did not come to a complete standstill, but could be continued to a lesser extent and, in some cases, almost to the same degree as before March 2020. Our data on the activities for the second and third pandemic year thus differ overall from a quantitative survey on the impact of the COVID-19 pandemic on the activities of civic associations in 2020, that is, in the first pandemic year (Hutter et al 2021). Here, it was found that activities in the areas of recreation, education, counseling, culture, and protest had to be severely restricted or stopped altogether.…”
Section: Discussionmentioning
confidence: 59%
“…Research on the impact of COVID-19 on civil society associations in Germany primarily refer to secular organizations and initiatives (Hutter et al 2021; Krimmer et al 2020; Schrader 2021). Studies have shown that the pandemic caused ambivalent and different effects regarding the extent to which organizations have been affected by the pandemic—depending on their resources, their level of professionalization, their operating ranges and target groups and, above all, their own initiative and adaptability to primarily digital formats (Hörsch 2020; Hutter et al 2021; Krimmer et al 2020; Müller 2022; Schrader 2021). German studies on Christian communities focus on the pandemic effects on the usage and provision of online worship services and other digital proclamation formats, that is, on digitization dynamics (Hörsch 2020; Müller 2022; Reimann and Sievert 2021; Schlag and Nord 2021).…”
Section: Literature Reviewmentioning
confidence: 99%